Transforming Academic Libraries into Information Commons: A Proposed Model - Chaddha, Kavita; Kanjilal, Uma (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2022)
Objective – The main objective was to create an information commons (IC) model for the existing library with minimum structural changes to achieve maximum benefit. The subdivisions of the main objective were:to find out students' expectations and perceptions of an ideal learning environment; to find out the factors which influence the satisfaction level of the students for the library; to find out how satisfied are students from the existing library; and to find out the current library usage pattern of the students.Methods – Based on the available literature on the topic, an online questionnaire survey was constructed with Google Forms and sent to current cohorts studying at the institute through e-mail, along with the study's rationale and a request for participation. We contacted 294 students, of which 199 responded. The data were analyzed and presented using Microsoft Excel.Results – The findings of the study showed the keen interest of the students in library resources and services. It also showed that the students were not fully satisfied with the current library space and working hours. They wanted enhanced quiet areas and collaborative spaces where information experts help them use the current technology to improve their learning experience. Based on the gathered data analysis, an IC model for redesigning the existing library has been recommended.Conclusion – The present study was the first step in research on ICs in the Indian context. This pilot study captured the perception and expectations of all levels of students: postgraduate, working executives, and senior-level executives. Most of the suggestions have been incorporated into the plan. With very few construction changes and new furniture, this model can be easily implemented in a small academic library without discarding the old furniture.